(untitled) (Research, Society and Development, 2025)
The present research aimed to investigate and quantify the lipid yield obtained from sansão-do-campo using pressurized CO₂ under supercritical conditions, generating an extraction kinetic curve to evaluate the effects of process variables (thermodynamic parameters) and compare them with the extraction yield obtained using the traditional method (based on conventional organic solvents). Sansão-do-campo is known for its multifunctional therapeutic potential, acting in anti-inflammatory and antimicrobial processes, as well as its use in the treatment of conditions such as bronchitis and breast cancer. Two oil extraction methods were employed to obtain the lipid content from the sample: an organic solvent (ethanol) and carbon dioxide in a supercritical state. Ethanol achieved a 2% yield after 8 hours of extraction, while supercritical CO₂ achieved a 4% yield in only 80 minutes. The extraction process using supercritical CO₂ fluid stood out due to its significantly higher efficiency in terms of process duration. Quantitative analysis based on experimental statistics demonstrated that variations in thermodynamic variables (pressure and temperature) did not show statistically significant effects on the yield of the extraction using supercritical carbon dioxide. Previous studies have shown that pressurized liquid extraction can also be effective for different oilseed matrices, and the use of statistical methods is essential to experimentally validate yields in extraction processes.